Surface functionalization of dinuclear clathrochelates via Pd-catalyzed cross-coupling reactions: facile synthesis of polypyridyl metalloligands. Issue 20 (25th April 2016) - Marmier, Mathieu; Cecot, Giacomo; Curchod, Basile F. E.; Pattison, Philip; Solari, Euro; Scopelliti, Rosario; Severin, Kay
Abstract : Clathrochelates can be decorated with pyridyl groups by cross-coupling reactions. They represent interesting ligands for supramolecular chemistry and materials science. Abstract : Dinuclear clathrochelate complexes are easily accessible by reaction of zinc(ii ) triflate or cobalt(ii ) nitrate with arylboronic acids and phenoldioximes. The utilization of brominated arylboronic acids and/or brominated phenoldioximes allows preparing clathrochelates with two, three, five or seven bromine atoms on the outside. These clathrochelates can undergo Pd-catalyzed cross-coupling reactions with 3- and 4-pyridylboronic acid to give new metalloligands featuring up to seven pyridyl groups. The pyridyl-capped clathrochelates display characteristics which make them interesting building blocks for structural supramolecular chemistry: they are rigid, large (up to 2.7 nm), luminescent (for M = Zn), and anionic. The pentatopic pyridyl ligands display an unusual trigonal bipyramidal geometry.